Contratualismo e a noção moral de agregação - Oliveira, Gustavo Oliva de (2022)
The subject of this dissertation is the relationship between moral contractualism and the notion of moral aggregation. Three main objectives follow. First, providing a detailed explanation of moral aggregation and its main problems. The main objection is that aggregative theories are incapable of making moral distinctions related to the separateness of persons. The second objective is offering a non-aggregative theory of morality, which will be moral contractualism, as a solution for aggregation’s problems. Contractualism is centered on moral justification and that is why it can account for cases in which aggregative theories fail. The third and last objective is defending moral contractualism from objections concerning its exclusion of aggregative clauses. Two forms of critique are examined: (i) the Numbers Problem, related to the troubles non-aggregative theories have when trying to explain cases that envolve saving lives, in which numbers matter from a moral standpoint; and (ii) social risk cases, in which risky actions are justified thanks to the relationship between benefits and degrees of risk. Contractualism is properly modified so that it can be defended from both kinds of objection.